2018
DOI: 10.3390/md16100353
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Hepatic Protein Carbonylation and Oxidative Stress Occurring on Diet-Induced Metabolic Diseases through the Supplementation with Fish Oils

Abstract: The present study addressed the ability of long-chain ω-3 polyunsaturated fatty acids (ω-3 PUFA), i.e., eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), to ameliorate liver protein damage derived from oxidative stress and induced by consumption of high-caloric diets, typical of Westernized countries. The experimental design included an animal model of Sprague-Dawley rats fed high-fat high-sucrose (HFHS) diet supplemented with ω-3 EPA and DHA for a complete hepatic proteome analysis to map carbonylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 45 publications
4
33
1
Order By: Relevance
“…The level of protein carbonylation is one of the indexes of protein damage caused by oxidative stress [26]. In our experiments, contrary to the lipid peroxidation, the difference in the protein carbonylation was not registered in any of experimental groups.…”
Section: Lipid Peroxidation and Protein Carbonylationcontrasting
confidence: 77%
“…The level of protein carbonylation is one of the indexes of protein damage caused by oxidative stress [26]. In our experiments, contrary to the lipid peroxidation, the difference in the protein carbonylation was not registered in any of experimental groups.…”
Section: Lipid Peroxidation and Protein Carbonylationcontrasting
confidence: 77%
“…The decrease in plasma IL-6 in rats receiving the combined supplementation compared to those fed the STD diet might be explained by the distinct fatty acid composition of the dietary backgrounds (STD or HF) and the use of fish oil instead of soybean oil. As we previously reported in the same cohort of rats [32], the STD diet increases the ω-6 PUFA content in the liver compared to the HF diet. The soybean oil is rich in linoleic acid (LA, 18:2 ω-6) (Table S3), which is a precursor of arachidonic acid (ARA, 20:4 ω-6) [55].…”
Section: Discussionsupporting
confidence: 81%
“…It is well-known that dietary ω-3 PUFA and its oxidized metabolites exert antioxidant effects in humans [ 24 ], probably by activating the nuclear factor-erythroid 2-related factor 2 signaling pathway [ 62 , 63 ]. Indeed, previous studies have shown that ω-3 PUFA supplementation attenuates the increase in the GSSG/GSH ratio and the content of protein carbonyls in the liver induced by excessive fat intake in rodents [ 32 , 38 ], which is accompanied by enhanced insulin sensitivity [ 38 ]. Furthermore, Selenscig et al [ 37 ] have shown that replacing corn oil as a dietary fat source with fish oil improves the epididymal adipose tissue function in rats fed a diet rich in sucrose by increasing antioxidant defenses and reducing ROS production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased level of ROS and disturbed redox signaling results in the oxidative damage on biomolecules in living systems. Many disorders which can trigger cancer or metabolic diseases are closely correlated with oxidative stress 3,4 .…”
mentioning
confidence: 99%